Trial implementation of CIRCuiTS cognitive remediation therapy for people with schizophrenia in Orange, New South Wales. (30th October 2019) - Thomas, Matt; Rusten, Kim
Abstract: Objective: Many people with schizophrenia experience cognitive impairments and current practice guidelines recommend cognitive remediation therapy. This implementation trial examined aspects of feasibility, acceptability and outcomes of the computerised interactive remediation of cognition—interactive training for schizophrenia cognitive remediation therapy program in our local context. Design: A longitudinal design was utilised with participants providing outcome data at commencement of the computerised interactive remediation of cognition—interactive training for schizophrenia program, completion and at follow‐up 3 months later. Setting: Our trial was conducted in the inpatient and community mental health contexts within the New South Wales regional city of Orange, between January 2017 and December 2018. Participants: Fifty‐three adult volunteers commenced the computerised interactive remediation of cognition—interactive training for schizophrenia program and participated in this trial. Forty‐five participants were currently admitted to psychiatric rehabilitation inpatient units at Bloomfield hospital, and eight were referred by Orange Community Mental Health Service. Main outcome measure(s): Participants completed measures of cognitive functioning (repeatable battery for the assessment of neuropsychological status), functional independence (Adaptive Behaviour Assessment Scales 3) and Goal attainment scaling. Results: Most participants reported they liked computerised interactive remediation of cognition—interactive training for schizophrenia therapy and made excellent progress towards their goals. Those who completed the program made significant gains in the domains of attention, memory and independence in key aspects of daily living. Gains in functional independence were sustained for a small sample following program completion. Conclusion: This implementation trial showed the computerised interactive remediation of cognition—interactive training for schizophrenia cognitive remediation therapy program was feasible, acceptable and contributed to strong outcomes in both the inpatient and community contexts. Efforts are in progress to translate the computerised interactive remediation of cognition—interactive training for schizophrenia program, and future research will focus on longer term outcomes, cost‐benefit analyses and the experiences of participants and therapists.